Miologia do membro pélvico da paca (Cuniculus paca Linnaeus, 1766) - Leal, Leonardo M. (2015)
This study aimed to describe the muscles of the pelvic limb of paca (Cuniculus paca Linnaeus, 1766) through anatomical dissection of this region. We used ten adult pacas, males and females, weighing 5 to 10 kg from the group of pacas at the sector of wild animals of FCAV, Unesp-Jaboticabal, SP. The animals were fixed with 10% formaldehyde and preserved in 30% saline solution for anatomical dissection of the pelvis, thigh and leg musculature, with identification of the origin and the insertion of each muscle. Photos were taken and the results were discussed based on the domestic animal, rat and guinea pig literature. In general, the paca musculature resembles the one of domestic animals and other rodents; but some variance in origin and insertion of each muscle and in the fusion of some muscular groups of the bellies was observed.